Estrutura populacional e história filogeográfica da toninha (Pontoporia blainvillei) - Santos, Elenara Verás dos (2011)
Franciscana (Pontoporia blainvillei) is the only extant representative of the Pontoporiidae family. This species occurs along the Atlantic coast of South America from Itaunas, Espirito Santo in Brazil to Golfo Nuevo, Valdes Peninsula in Argentina. The most important threat to the species is the accidental by-catch that in some places reached the number of 1000 related events per year. In recent years an increasingly number of studies had revealed the existence of considerable genetic variation along the geographical distribution of P. blainvillei. In this study, looking to collaborate towards a better comprehension of such existing structure, we analyzed new molecular data, including the sequencing of mitochondrial DNA control region and 11 microsatellite loci from 253 individuals along the Brazilian, Uruguayan and Argentine coast. For the mitochondrial DNA analysis, we added sequences previously deposited in GenBank, totalizing 512 sequences. Results obtained based on the two molecular markers revealed a clear differentiation of the species in three main groups: (1) Rio de Janeiro / Espirito Santo, (2) Sao Paulo and north of Santa Catarina, and (3) south of Santa Catarina, Rio Grande do Sul, Uruguay and Argentina. The study also shows alarming estimates in reference to the effective size of some populations, mainly from Rio de Janeiro/Espirito Santo which will probably reflect on its conservation status. These results supports the definition of the four management areas (Franciscana Management Area - FMAs) previously suggested by Secchi and associates in 2003, and point out the importance of this definition to the conservation of the genetic diversity of the species.